Virtualni inženiring I.: Komponente virtualnega inženiringa, zapiski predavanj - Hren, Gorazd (2024)
Virtual Engineering I.: Virtual Engineering Components, Lecture Notes. The publication is intended for students who are daily and increasingly experience the use of development computer tools in product design. High-quality and more complex computer applications enable simulations and analyses of engineering solutions before they are implemented as prototypes or final products. Virtual engineering is firstly formed by geometry creation components, CAD systems and reverse engineering with scanning systems, which forms the basis for further product development processes. The next components are the production of virtual prototypes in a virtual environment or physical prototypes, the production of which is nowadays mostly performed by 3D printing. Numerical simulations are extremely important in product development, which enable analyses of strength, fluid dynamics and movement of mechanisms based on boundary conditions. With the obtained information, we can plan production, logistics, quality control, ergonomics, and marketing before the product goes into final production. All these components are linked by DMU, PLM information systems, which enable and also determine the organisational structure of the development work described in the last chapter: Virtual product development.
Keywords: virtual engineering; CAD systems; reverse engineering; numerical simulations; virtual product development